Community forestry: Cultivate new markets - Hill, Tony (Technical Centre for Agricultural and Rural Cooperation, 2011)
Farmers in the area around Tominian in Mali use cell phones and radio adverts to sell non-timber products from local trees, and supplement their income from agriculture